Discovery of anti-methicillin-resistant Staphylococcus aureus inhibitors by targeting thymidylate kinase (TMPK) via multi-step virtual screening, molecular simulations, and free energy calculations - Talal Alshammari; Abdulrahman Alshammari; Metab Alharbi; Abdullah F. Alasmari; Abdullah S. Alhamed; Norah A. Albekairi; Alanoud Talal Aljasham; Amal F. Alshammary (Journal of Infection and Public Health, 2025)
Background: Antibiotic resistance, mainly caused by methicillin-resistant Staphylococcus aureus (MRSA), is a globally growing concern and a significant health issue in regard to infectious diseases. This issue will require a novel and comprehensive strategy to overcome the resistance to MRSA. Methods: Therefore, the current study advances TMPK-targeted drug discovery by screening a vast chemical space using virtual screening with detailed dynamics and binding energy evaluations. In contrast to the previous efforts, our study focuses on the pharmacological exploitation of TMPK's conserved and druggable active site in MRSA, which lacks homologs in humans and remains understated in antimicrobial pipelines. We screened traditional Chinese medicine and African natural compound databases, as well as the InterBioScreen, dark chemical matter, and Maybridge databases, using a three-step virtual screening strategy. Results: From these databases, we identified 16 compounds as the most potent based on their docking and redocking scores and interaction profiles with the key residues. Of these, the top eight hits were re-validated using the induced-fit docking method, which confirmed the validity of these hits’ interaction and inhibitory potential against TMPK. Thereafter, using molecular simulations, 500 ns each, we determined that these compounds exhibited stable dynamic profiles, minimal residual fluctuation, and well-folded conformations during the simulation. Furthermore, using the binding free energy calculations, including both the MMGBSA and MMPBSA methods, the top hits were ranked based on the strongest binding energy, which provides compelling evidence for the stability, specificity, and high binding affinity of these compounds towards TMPK. PCA (Principal Component Analysis) and FEL (Free Energy Landscape) analyses revealed the conformational behavior of these complexes. Furthermore, ADMET analysis confirmed the safety of these molecules. Conclusions: This study identified potential therapeutic hits using computational and theoretical approaches; however, experimental validation through in vitro enzymatic assays and MRSA culture-based inhibition studies is essential to confirm their therapeutic potencies.